Relationship of ethylene production on climacteric behavior in guava (Psidium guajava L.) leaf disks - Seephueng, Tanyakan; Shiesh, Ching-Chang (วารสารผลิตกรรมการเกษตร, 2019)
Guava (Psidium guajava L.) is a climacteric fruit although some cultivars behave in a non-climacteric manner. The objective of this work was to study about the ripening process in guava leaf disks by using kinetin induce ethylene for reduce time of selection and breeding. The results revealed that after 72 hours of incubation, the ethylene production greatly increased in climacteric cultivars and negligible in non-climacteric cultivars. The respiration rates in most cultivars were hardly different. It was predicted that respiratory pattern in hybrid seedlings from ‘Pakistan’ (Climacteric pattern) and ‘Shyh-Jii Bar’ (Non-Climacteric pattern) would eventually be climacteric. Moreover, it was also predicted that respiratory pattern in hybrid seedlings from ‘Hawaii’ (Climacteric pattern) and ‘Jen-Ju Bar’ (Non-Climacteric pattern) would be non-climacteric. The respiration rates were hardly different in all of cultivars. Therefore, ethylene production could be used as an index of climacteric manner to classify the cultivars of guava as either climacteric or non-climacteric type.